Does size matter? The benefits and challenges of voluntary sector partnerships in dementia service provision for South Asian communities in England. (7th July 2016) - Blakey, Heather; Parveen, Sahdia; Oyebode, Jan R.
Abstract : In response to the need for improved access to dementia services for minority ethnic communities, the Alzheimer's Society piloted, in 2014, the Information Programme for South Asian Families (IPSAF), an adapted version of its existing course for carers. It delivered this in partnership with local black and minority ethnic community and faith organisations, a new approach for the Alzheimer's Society. In most cases, the partnerships formed were strong and effective, and have given rise to ongoing plans for joint working that bring benefits to both the local organisations and the Alzheimer's Society. However, the current realities of UK voluntary and community sector dynamics raise questions of ownership and issues around how to establish genuine partnerships. In this article, we reflect on what the IPSAF experience indicates about the potential for equitable partnerships between small and large organisations, and draw out lessons for building effective, mutually beneficial relationships.